Amyloid-beta and Alzheimer’s disease: the role of neprilysin-2 in amyloid-beta clearance - Marr, Robert A.; Hafez, Daniel M. (Frontiers in Aging Neuroscience, 2014)
Accumulation of the amyloid-beta (Ab) peptide is a central factor in Alzheimer’s disease (AD) pathogenesis as supported by continuing evidence. This review concisely summarizes this evidence supporting a critical role for Ab in AD before discussing the clearance of this peptide. Mechanisms of clearance of Ab are critical for preventing pathological elevations in Ab concentration. Direct degradation of Ab by endopeptidases has emerged as one important pathway for clearance. Of particular interest are endopeptidases that are sensitive to the neprilysin (NEP) inhibitors thiorphan and phosphoramidon (i.e. are “NEP-like”) as these inhibitors induce a dramatic increase in Ab levels in rodents. This review will focus on Neprilysin-2 (NEP2), a NEP-like endopeptidase which cooperates with NEP to control Ab levels in the brain. The evidence for the involvement of NEP2 in AD is discussed as well as the therapeutic relevance with regards to gene therapy and the development of molecular markers for the disease.